2002
DOI: 10.1038/labinvest.3780409
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evaluation of a Phosphorothioate Oligonucleotide in the Retina of Rhesus Monkey

Abstract: SUMMARY:Overexpression of vascular endothelial growth factor (VEGF) has been strongly implicated in the development of choroidal neovascularization (CNV) in patients with age-related macular degeneration. In this study, a phosphorothioate oligonucleotide (PS-oligo) targeting both human and rat VEGF 165 genes upstream of the translation initiation code, named DS135 in this study, was evaluated for its uptake dynamics and retinal tolerance after intravitreal (IV) and subretinal (SR) injections in the rhesus monk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 36 publications
2
33
0
Order By: Relevance
“…[6][7][8][9][20][21][22] Several studies have further shown that inhibition of VEGF activity by administration of VEGF-specific kinase inhibitors, VEGF antibodies, VEGF receptors and VEGF antisense oligonucleotides successfully suppressed the development of retinal and choroidal NV. [37][38][39][40] In particular, Honda et al 41 showed that expression of adenovirus-mediated sFlt-1 suppressed choroidal NV. However, the adenoviral vector was injected into the rat femoral muscle resulting in systemic circulation of sFlt-1, which dropped to very low levels after 21 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][20][21][22] Several studies have further shown that inhibition of VEGF activity by administration of VEGF-specific kinase inhibitors, VEGF antibodies, VEGF receptors and VEGF antisense oligonucleotides successfully suppressed the development of retinal and choroidal NV. [37][38][39][40] In particular, Honda et al 41 showed that expression of adenovirus-mediated sFlt-1 suppressed choroidal NV. However, the adenoviral vector was injected into the rat femoral muscle resulting in systemic circulation of sFlt-1, which dropped to very low levels after 21 days.…”
Section: Discussionmentioning
confidence: 99%
“…Previous attempts using VEGF antisense oligonucleotides, soluble Flt-1-chimeric proteins and adenovirus-mediated sFlt-1 also failed to completely block retinal or choroidal NV, achieving only a maximum inhibition of 50%. 37,38,40,41 In contrast, administration of kinase inhibitors that blocked phosphorylation by VEGF and platelet-derived growth factor (PDGF) receptors completely prevented the development of retinal NV, but kinase inhibitors of PDGF receptors alone had no effect. 39 Although this implies that blockade of VEGF activity alone is sufficient for the complete inhibition of NV, a synergy might exist between VEGF and PDGF, or other angiogenic factors, which all need to be blocked concurrently for complete inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…The injection procedure was performed under aseptic conditions in a surgical theater equipped for non-human primates. The left eyes of eight non-human primates were subretinally injected with AAV2.sFlt-1 (n ¼ 5), recombinant sFlt-1 protein (n ¼ 1, Cell Sciences, Boston, MA, USA) or AAV2.GFP (n ¼ 2), as previously described, 11,61 but with modifications to the microdelivery system. A 41-gauge subretinal cannula (Bausch and Lomb, Rochester, NY, USA), shortened and fashioned into a bevel tip to allow easier access into the subretinal space, was connected to a flexible pediatric tubing that was in turn connected to a 5-ml syringe.…”
Section: Animal Preparation and Anesthesiamentioning
confidence: 99%
“…The 100 ml virus-or proteincontaining solution was injected into the eye to create a subretinal bleb with a size of about four times the optic disc diameter, as described previously. 11,61 One uninjected non-human primate was used as control.…”
Section: Animal Preparation and Anesthesiamentioning
confidence: 99%
“…In addition, this ODN-1 injected intravitreally in an animal model of CNV led to the attenuation of CNV, as assessed by fluorescein angiography. 73 CNV was induced by laser photocoagulation. 74 The synthesis and use of lipophilic amino acid dendrimers (lipid-lysine) to deliver ODN-1 was accomplished.…”
Section: Dendrimers and Age-related Macular Degenerationmentioning
confidence: 99%